Proposta de mitigação para radônio em água de poço da região do pinheiro em Curitiba/PR. - Paschuk, Sergei Anatolyevich (2013)
This paper presents a proposal for mitigation of 222 Rn using the process of aeration of the water and analyzing the concentration of radon in well water. It was analysed 10 samples of well water collected in the region o Pinheirinho in Curitiba, Paraná St. Measurements were performed using with the Professional Radon Monitor AlphaGUARD (SAPHYMO), that provides radon measurmentes in the range of 2 - 2x10 6 Bq/L. The concentration levels of 222 Rn were measured by appropriate formulations considering the decay time due the delay in collecting the samples and the measurements. The method used was the mitigation of aeration, called Diffusion Aeration. The process of degassing occurs by injecting air through an aerator connected to a porous plate during the four days. The samples showed concentrations of 222 Rn approximately 40 Bq/L, value that is above 11.11 Bq/L recommended by the USEPA (Environmental Protection Agency of the United States). After applying the mitigation procedure Paschuk et al in the water samples, the concentrations of 222Rn decreased to a level lower than expected by the natural decay of the gas.